Pulse electric field exposure effect on morphological properties of HeLa cells - Adon, Mohamad Nazib (2015)
This thesis is concerned with the investigation of pulsed electric field (PEF) towards biological cells. Biological cells selected in this study are HeLa (cervical cancer) cells. There are two parts of the study, which was involving modeling methods and experimental setup. Modeling method used involves analytical (MATLAB) and numerical (CST®EMS) methods. Both of these methods are to prove the existence of the effect on transmembrane potential changes when subjected exposed to PEF strength. This result can be seen clearly when both method showed the existence of changes effects on transmembrane potential. Therefore, this study continues by identifying an appropriate experimental setup. Experimental setup involves four important parts, the first part is the source of square wave PEF (ECM®830) that can generate until 3kV field strength. Followed by modified EC magnetic chamber with incubator system that has been used in order to exposed HeLa cells to PEF. At the same time this system is coupled with Nikon inverted microscope (Ti-series) for subsequent visualization techniques, image and video. In the early stage, experimental setup was tested by monitoring the proliferation rate of HeLa cells within 0 to 48 hours. Then HeLa cells were tested to look at the swelling effect via PEF exposure. After that, we continued to identify the optimum PEF parameters for reversible condition on HeLa cell. As a result HeLa cells gives a good response at 2.7kV field strength, 30μs pulse length with single pulse. Further study showed that two or more adjacent HeLa cells merge together due to increased cell membrane permeability (electrofusion). This discovery triggered an idea to look at the PEF effect on wound healing process. An artificial wound site were investigated with and without PEF exposure. The finding shows PEF exposed wound area took 3 hours to completely heal while the untreated area took 10 hours. This prove a novel technique (electrical based novel treatment) which could be an alternative to drug usage for wound healing process. Overall, the findings achieved in this study could lead us onto a drug free wound healing method.